The Visual Structure of 19th Century Batavian Indigenous Women - Casande, Suwito; Martyastiadi, Yusup Sigit (Universitas Multimedia Nusantara, 2024)
This research used material objects in the form of indigenous Batavian women's clothing worn in the 19th century (1870-1930). Clothing at this time was used as a social marker based on ethnicity. This research used the symbolic interactionism paradigm, and the analysis of clothing structure was carried out formally regarding the main clothing, millineries, and accessories. The interpretation used Anthony Gidden's theory to see the formation of structures and agents. This research concluded that indigenous women in the 19th century had a significant role in shaping the type and quality of clothing in the Dutch East Indies. Indigenous women in the 19th century were not only users but were also involved in creating fashion for the people of Batavia. Keywords: clothing; indigenous women; batavia; colonial